1989
DOI: 10.1007/bf00199213
|View full text |Cite
|
Sign up to set email alerts
|

Augmented induction of antitumor cells in vivo by cyclophosphamide fails to benefit antitumor resistance of the host

Abstract: The present study was designed to examine whether cyclophosphamide augmented induction of antitumor cells and antitumor resistance in C57BL/6 mice pretreated with mitomycin-C-treated EL4 cells (EL4MMC) plus OK-432, a streptococcal preparation. C57BL/6 mice were pretreated with EL4MMC (10(7] plus OK-432 (2.5 KE) i.p. twice at 1-week intervals. When the mice received an i.p. injection of cyclophosphamide at 200 mg/kg 2 days before the last treatment, the antitumor activity of their spleen cells and peritoneal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This study shows that L-arginine-dependent nitric oxide was a major media-tor of antitumor activity of macrophages induced with OK-432 and CY. This supports our previous study [21] that increased and persistent induction by CY treatment of antitumor macrophages is not beneficial to antitumor resistance by the host. Meanwhile, Stuehr and Marletta [25,26] have reported that lipopolysaccharide or bacillus CalmetteGurrin treatment dramatically increases nitrate levels in blood and urine of treated mice and that macrophages are responsible for this nitrate biosynthesis in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study shows that L-arginine-dependent nitric oxide was a major media-tor of antitumor activity of macrophages induced with OK-432 and CY. This supports our previous study [21] that increased and persistent induction by CY treatment of antitumor macrophages is not beneficial to antitumor resistance by the host. Meanwhile, Stuehr and Marletta [25,26] have reported that lipopolysaccharide or bacillus CalmetteGurrin treatment dramatically increases nitrate levels in blood and urine of treated mice and that macrophages are responsible for this nitrate biosynthesis in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…EL4 tumor cells were maintained in vivo and in vitro as previously described [21]. L929 cells were maintained by culturing in Eagle minimum essential medium (Nissui Seiyaku Co., Tokyo) with 10% fetal calf serum and 2 mM L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations